APPLICATION OF THE GREEN TOURISM CONCEPT IN THE BOGOR BOTANICAL GARDENS IN SUPPORTING SUSTAINABLE TOURISM DEVELOPMENT - Fauzia Salma Effendy (Sean Institute, 2023)
Green Tourism or can be interpreted as Green Tourism is a tourism concept that is gaining popularity among the tourism industry as a form of stakeholder responsibility in supporting sustainable tourism. Bogor Botanical Gardens, known as a green open space in the city of Bogor, is a tourist attraction that implements the Green Tourism concept. This concept was initiated to support sustainable tourism development by maintaining the sustainability and beauty of Bogor Botanical Gardens and maintaining the vision to become a center of excellence for conservation. This research uses a qualitative approach with descriptive methods. The data collection technique used is library research (Library Research). The results of this study indicate that the participation of Bogor Botanical Gardens through the implementation of Green Tourism is as follows: 1) Potential tourism objects for Bogor Botanical Gardens are natural beauty, socio-culture and artificial tourism with the concept of green open spaces or landscapes; 2) The role of the central and regional governments is to make policies and supervise the development of Bogor Botanical Gardens; 3) Managers and the national Research and Innovation Agency contribute to creating tourism programs and preserving the environment of Bogor Botanical Gardens; 4) The application of Bogor Botanical Gardens Green Tourism in supporting sustainable tourism is by maintaining the concept of green open space which helps managers also to promote the Bogor Botanical Gardens as a natural tourist object that restrains sustainable tourism development.